Perbedaan Vo2Max Pada Perokok Yang Tinggal Di Daerah Pegunungan Dan Dataran Rendah Di Kabupaten Boyolali - Saptono, Dwi; , Wahyuni, S.FT,M.Kes (2016)
Background: Accumulated kanduangan smoke in the lungs can reduce lung elasticity which causes lung vital capacity decreased. The decline in vital capacity of the lung can result in reduced oxygen supply to the tissues. The condition, plus the living conditions will affect the person's physiology. PO2 difference between mountainous areas and lowlands will affect hemoglobin levels and lung capacity, both of which are a deciding factor VO2max values. Objective: To menggetahui VO2max difference in smokers who live in the area pegununggan and low-lying areas in the district boyolali. Methods: This study is a research type of research is an observational study, with crosss sectional approach. The study design using one test shoot. Results and Conclusions: The analysis of this study using the test shepiro Wilk test on a group of smokers who live in the area pegununggan and smokers who live in low-lying areas .. The group of smokers area pegununggan acquire wherein p = 0.628 (p> 0.05). While the group of smokers who live in the lowlands acquire wherein p = 0.683 (p> 0.05), which means that there are differences in VO2max values in smokers who live in the area and smokers pegununggan low-lying areas in the district Boyolali.ini mean normal distribution so that the data this qualifies using T test test. In the test the difference of using Independent-sample T test obtained by value t = 2,661 0,010 denggan significant figures. Due to the significance of the numbers is less than 0.05, then conclude that there are no differences in VO2max in smokers who live in low-lying areas in pegununggan and Boyolali districts.